Collective Memory from a Psychological Perspective. Issue 5 (May 2018) - Hirst, William; Yamashiro, Jeremy K.; Coman, Alin
Abstract : Social scientists have studied collective memory for almost a century, but psychological analyses have only recently emerged. Although no singular approach to the psychological study of collective memory exists, research has largely: (i) explored the social representations of history, including generational differences; (ii) probed for the underlying cognitive processes leading to the formation of collective memories, adopting either a top-down or bottom-up approach; and (iii) explored how people live in history and transmit personal memories of historical importance across generations. Here, we discuss these different approaches and highlight commonalities and connections between them. Highlights: Collective memories can involve small communities, such as couples, families, or neighborhood associations, or large communities, such as nations, the world-wide congregation of Catholics, or terrorist groups such as ISIS. They bear on the collective identity of the community. Many studies focus on either the representation of extant collective memories or the formation and retention of either extant or new collective memories. Those interested in the formation of collective memories can approach the topic in a top-down or bottom-up fashion. Other studies explore the relationship between personal or autobiographical memories and historical memories. How do people live in history? How do they pass down their experiences from one generation to the next?